EDUCATION REFORM IN THE REPUBLIC OF UZBEKISTAN: MODERN SCHOOLS AND MODERN EDUCATION. - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article describes the legal framework for reforms in the education system of the republic. The significance and goals of the reforms in the field of education implemented in the years of independence of Uzbekistan